Kajian Normatif Konsep Wawasan Lingkungan Dalam Perlindungan Satwa Langka Indonesia Berdasarkan Konvensi Cites - Moh Lutfi Rohman; Lintang Aga Sekarsari (FAIRNESS AND JUSTICE, 2020)
With no control over the problems that threaten the extinction of endangered species in the world. An organization whose job is to provide protection for animals, which is named the International Union for Conservation of Nature andNatural Resources (IUCN) formed and signed the CITES (Convention on International Trade in Endangered Species of Wild Fauna and Flora), which is an International agreement related to protection and international trade in endangered species of wild animals and plants. Illegal wildlife trade threatens Indonesia biodiversity. CITES indirectly becomes a consideration foe making national rules. Therefore Indonesia has ratified CITES through Presidential Decree No.43 of 1978 and established Law No.5 of 1990 concerning Biological Natural Resources and their Ecosystems, as well as through BKSDA, as the executor of the task of carrying out conservation and overcoming free trade of endangered species.